Pengembangan Petunjuk Praktikum Biologi Berbasis QR Code Bagi Siswa SMA - Houtba, Wanodyata Tritania; Fitriani, Linna; Jayanti, Ria Dwi (LPPM Politeknik Raflesia, 2025)
Education is an activity carried out to make changes for the better, especially in the behavior of students. Learning that uses teaching materials that support existing technology with familiar environmental conditions around students is expected to add to the experience of the student learning process so that it is more interesting and useful. The study aims to determine the validity and readability of QR Code-based practical instructions on the test of Kersen Leaf essence (Muntingia calabura) against the inhibition zone of Pseudomonas aeruginosa. The method used is Research & Development Borg & Gall. Descriptive data were obtained from criticism and suggestions from validators and student trial respondents. The research instruments used were validation sheets and questionnaires. Furthermore, the data that has been obtained is analyzed to obtain its validity value. The results of the development of QR Code-based practical instructions that have been carried out, the results of validation by three validators, namely media experts with a percentage value of 83.33%, language experts with a percentage value of 93.75%, material experts with a percentage value of 85%, teachers with a percentage value of 92.5% and student readability tests with a percentage value of 92.7%. So the results of the validation and readability test indicate that the QR Code-based practical instructions developed are very valid and feasible to use.